The Problems of Health Development in Indonesia: A Study from a Decentralized Governance Perspective - Sudarwanto, AL Sentot; Kharisma, Dona Budi (International Journal of Criminology and Sociology, 2022)
Health sector in Indonesia faces many complex challenges. The enactment of the new regional government legislation has resulted in a decentralization policy design that requires the regional government to cover all the health issues. Besides, the policy on health issues is also influenced by the many changes of national strategic environment. Many findings indicate apprehensive situations in the health sector. Some of the problems include health financing, health personnel, and health regulations. Thus, it is recommended that each regional government develop a Regional Health System (RHS) as the implementation of health policy.